Behavioural preferences and labour market attachment among South African youth - Goddard, Ianthe (School of Economics, 2025)
Youth unemployment in South Africa remains a persistent and multifaceted challenge. This study explores how behavioural preferences—specifically risk aversion and probability weighting—vary across employment categories among South African youth. Using structural estimates from incentivised Multiple Price List (MPL) tasks, we estimate parameters for relative risk aversion (r) and probability sensitivity (γ) and examine how these relate descriptively to wage employment, self-employment, and unemployment. Our findings suggest that employed females exhibit higher levels of risk aversion, consistent with a preference for stable income under constrained structural conditions. Unemployed individuals, particularly those exhibiting back-switching behaviour in MPL tasks, display more curved or non-linear probability weighting. We interpret lower γ values not as psychological pessimism or irrationality, but as reduced sensitivity to probability - potentially a bounded rationality response to uncertainty and limited feedback. We do not infer causality, but highlight how behavioural regularities correlate with labour market status in a high-uncertainty, developing-country context. Our results contribute to the behavioural economics literature by extending models of bounded rationality to explain labour market disengagement. The findings offer preliminary policy insight into how informational environments and employment support structures could be designed to improve labour market participation among youth